2019
DOI: 10.3390/cancers11030370
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy of Chloroquine and C2-Ceramide Enhances Cytotoxicity in Lung Cancer H460 and H1299 Cells

Abstract: Non-small cell lung cancer (NSCLC) is a type of malignant cancer, and 85% of metastatic NSCLC patients have a poor prognosis. C2-ceramide induces G2/M phase arrest and cytotoxicity in NSCLC cells. In this study, the autophagy-inducing effect of C2-ceramide was demonstrated, and cotreatment with the autophagy inhibitor chloroquine (CQ) was investigated in NSCLC H460 and H1299 cells. The results suggested that C2-ceramide exhibited dose-dependent anticancer effects in H460 and H1299 cells and autophagy induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Based on this knowledge, in vivo studies have started to employ autophagy inhibitors, such as inhibitors of the lysosomal protease and anti-malaric drugs, Chloroquine (CQ) or Hydroxichloroquine (HCQ), to treat cancer, more often in combination with chemotherapies able to induce autophagy [1719]. Such combinations, mainly used to treat cancer in xenograft mouse models, have registered some successes in controlling tumor growth and prolonging host survival [2022]. However, in order to avoid tumor rejection, immune deficient mice have been used for these experiments, thus cutting out the possibility to explore the direct and indirect role of autophagy inhibitors on the cells of the immune system [8].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this knowledge, in vivo studies have started to employ autophagy inhibitors, such as inhibitors of the lysosomal protease and anti-malaric drugs, Chloroquine (CQ) or Hydroxichloroquine (HCQ), to treat cancer, more often in combination with chemotherapies able to induce autophagy [1719]. Such combinations, mainly used to treat cancer in xenograft mouse models, have registered some successes in controlling tumor growth and prolonging host survival [2022]. However, in order to avoid tumor rejection, immune deficient mice have been used for these experiments, thus cutting out the possibility to explore the direct and indirect role of autophagy inhibitors on the cells of the immune system [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we also found that xanthohumol potentiates cisplatin apoptotic effects. Although new therapies for the treatment of lung cancer have evolved, NSCLC accounts for 85% of lung cancer cases and more than half of the cases are already metastatic at diagnosis [24]. While the treatment options and approaches for malignant lung cancer have evolved significantly, other factors such as secondary resistance is often associated with poor treatment successes and survival [24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Although new therapies for the treatment of lung cancer have evolved, NSCLC accounts for 85% of lung cancer cases and more than half of the cases are already metastatic at diagnosis [24]. While the treatment options and approaches for malignant lung cancer have evolved significantly, other factors such as secondary resistance is often associated with poor treatment successes and survival [24][25]. Platinum-based chemotherapy including cisplatin in combination with other chemodrugs still remains first line of treatment and has been shown to improve overall survival (OS) in comparison with other drugs such as carboplatin or newer chemodrugs [1,26].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Chou et al (17) revealed that cotreatment with CQ enhanced the cytotoxicity of C2-ceramide by 2.4-and 3.4-fold respectively compared with single treatment in the two NSCLC cell lines H460 and H1299; moreover, combination treatment significantly reduced the migration and invasion capability of both cell lines. Furthermore, in vivo analysis demonstrated that a combination of C2-ceramide and CQ resulted in a significant tumor-inhibition efficacy in the zebrafish xenograft model compared with single treatment groups, which suggests that the combination was reliable for lung cancer treatment (17). The present study investigated whether the autophagy inhibitor CQ can improve the sensitivity of the A549 lung cancer cell line to EPI, and attempted to elucidate the mechanisms involved.…”
Section: Introductionmentioning
confidence: 98%
“…Chloroquine (CQ) is a commonly used autophagy inhibitor that functions by disrupting the acidic environment of lysosomes and inhibiting the fusion of autophagosomes with lysosomes (16). A study by Chou et al (17) revealed that cotreatment with CQ enhanced the cytotoxicity of C2-ceramide by 2.4-and 3.4-fold respectively compared with single treatment in the two NSCLC cell lines H460 and H1299; moreover, combination treatment significantly reduced the migration and invasion capability of both cell lines. Furthermore, in vivo analysis demonstrated that a combination of C2-ceramide and CQ resulted in a significant tumor-inhibition efficacy in the zebrafish xenograft model compared with single treatment groups, which suggests that the combination was reliable for lung cancer treatment (17).…”
Section: Introductionmentioning
confidence: 99%